Indonesian EFL Students’ Views on Short-form Video Language Learning - Muhammad Indra Fathanul Hafizh; Iwan Setiawan; Syamdianita Syamdianita; Ichi Ahada (E3L: Journal of English Language Teaching, Linguistics, and Literature, 2025)
This study explored how Indonesian EFL students with different levels of short-form video (SFV) consumption perceived its impact on their English language proficiency. Using a qualitative phenomenological approach, three participants were selected based on their daily duration of English-language SFV usage. Data were collected through interviews, 7-day learning logs, and reflective journals. Findings indicated that all participants reported improvements in listening, speaking, and vocabulary, particularly through repeated exposure to authentic speech and mimicry. However, reading and writing development remained limited. Crucially, the study found that the quality of engagement—such as intentional mimicry, vocabulary tracking, and content curation—was more influential than the amount of time spent watching. Participants who used SFVs strategically experienced greater gains than those who consumed them passively. Additionally, attention span and distraction emerged as factors affecting learning depth, especially in high-exposure contexts. The study concluded that SFVs can support informal language learning when used purposefully and in moderation.